Quality of Financial Statements with the Application of Accounting Information Systems and Human Resources Competence - Sri Dewi Anggadini; Ari Bramasto; Muhamad Iqbal Adrian (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
This study aims to understand the quality of financial statements in several insurance subsidiaries in Bandung City, Indonesia considering several factors including the application of AIS (Accounting Information System) and Human Resource Competence. The method used in this research is the descriptive method and verification method. This research was conducted using primary data, by collecting data by distributing questionnaires using Proportional Random Sampling using the Slovin proportional formula, namely 60 respondents in several insurance subsidiaries. The statistical test used in this study is the Validity Test and Reliability Test as a first step, followed by the Classical Assumption Test. To know the relationship between several variables studied by utilizing the Multiple Linear Regression Test and the Correlation Coefficient Test. The last stage is the Coefficient of Determination Test and the t-Test. All data processing is carried out statistically using the SPSS program. The research results show the following: The existing system in the company can make employees perform their duties more efficiently. One of the indicators in the implementation of the AIS has the greatest influence on the Quality of Financial Reports. The implementation of AIS affects the Quality of Financial Reports. Financial Accounting Standards are accounting principles that are applied in preparing and presenting financial statements. One of the categories in Human Resource Competence occupies the highest influence on the Quality of Financial Statements. The benefit of this research is the belief that the quality results of the insurance company's financial statements are trusted. Customers can prevent the occurrence of non-payment of claims, the impact of the rise of insurance companies that has been going on since a few years ago that has not yet been resolved.